2019
DOI: 10.1017/s0030605319000012
|View full text |Cite
|
Sign up to set email alerts
|

Conservation conversations: a typology of barriers to conservation success

Abstract: Despite considerable achievements in the field of conservation, biodiversity continues to decline and conservation initiatives face numerous barriers. Although many of these barriers are well known, for example insufficient funding and capacity, there has been no systematic attempt to catalogue and categorize them into a typology. Because risks compromise the conservation mission, any barrier to success is a risk. Here we present the first attempt at identifying key barriers. We analyse extensive interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
(43 reference statements)
3
20
0
Order By: Relevance
“…Our first key finding was that professionals working internationally across continents concur with the barriers to conservation previously raised in face‐to‐face interviews with a predominantly African‐based conservationists (Sanders et al. ). The relative scores (Table ) of all barriers exceeded 50%, suggesting all were considered somewhat important.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our first key finding was that professionals working internationally across continents concur with the barriers to conservation previously raised in face‐to‐face interviews with a predominantly African‐based conservationists (Sanders et al. ). The relative scores (Table ) of all barriers exceeded 50%, suggesting all were considered somewhat important.…”
Section: Discussionsupporting
confidence: 64%
“…We believe some of these limitations were overcome by our original list of barriers (Sanders et al. ). It would, however, be interesting to repeat this study in future and compare results to see whether and how prioritization of barriers have changed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sanders et al (2021) interviewed conservationists (mostly from Kenya and South Africa) to produce a useful typology of the main barriers to conservation success. They found that the inability to demonstrate impact was the second most commonly cited barrier of the 74 identified.…”
mentioning
confidence: 99%